Banking on ICT: The relevance of online dispute resolution in the islamic banking industry in Malaysia - Oseni, Umar Aimhanosi (Routledge - Taylor & Francis Group, 2015)
In order to keep the cost of settling disputes low and standards for grievance remedial methods high, access to justice is paramount in today’s fast pace commercial transactions in the digital world. In Malaysia, the successes recorded in the Islamic banking industry do not just flourish without some consequential challenges such as the increasing rate of disputes involving Islamic financial products and services. Though the number of widely reported cases heard and determined by the courts between 1985 and 2010 are about 20, the Financial Mediation Bureau seems to be more active in dispute resolution in the industry. This study seeks to explore the relevance of such mechanism that would use five distinct but connected modules for dispute settlement. This pioneering research introduces a new dimension in the sustainability of the economy by leveraging the state-of-the-art information and communication technology (ICT) in resolving banking disputes in the Islamic finance industry in Malaysia. Exploring the relevance of such online dispute resolution platform for Islamic finance disputes will serve as a launch pad for further studies that will involve the design and application of such technology in the Islamic finance industry.